BANTUSAR WITH THE AHA 2020 GUIDELINE ON THE SKILLS OF HEALTH WORKERS AT LUKAS HOSPITAL BANGKALAN, EAST JAVA, INDONESIA - Haryanto, Agus; Mufarika, Mufarika; So'emah, Eka Nur (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2024)
Cardiac arrest is a critical condition that can be life-threatening where the condition of cardiac output is unable to meet the needs of oxygen to the brain and other vital organs suddenly and can return to normal if appropriate action is taken, BANTUSAR with AHA 2020 Guideline is one of the basic training for the skills of health workers in dealing with emergency problems due to trauma and cardiovascular disorders. Handling these problems is intended to provide basic life support so as to save lives and minimise organ damage and disability of sufferers. This research method uses Quasi Experiment Pre-Post Test Design. This research was conducted at Lukas General Hospital Bangkalan Madura, research data collection was carried out on 21 September 2024 with Total Sampling. Respondents in this study were all health workers at Lukas General Hospital Bangkalan, totalling 65 respondents. In the research process, researchers conducted a pre-test on the ability of health workers' skills in BANTUSAR using an observation sheet, then continued by providing an understanding of the latest BANTUSAR through training, and ended with a post-test. The collected data was then analysed using SPSS-10 with the Wilcoxon Signed Rank Test statistical test. The results of the Wilcoxone signed rank test statistical test showed a significance value / Sig. (2-tailed) ρ-value of 0.000 < α 0.05 with a Z value (-7.278), it can be concluded that H0 is rejected, which means that there is an influence between BANTUSAR and the AHA 2020 Guideline on the skills of health workers. By providing BANTUSAR training at Lukas Hospital Bangkalan Madura, it can improve the skills of health workers which is expected to be in line with patient satisfaction.